Reduction in the protein level and addition of oil in diets for finishing pugs under different temperatures - Nair Elizabeth Barreto Rodrigues (Revista Brasileira de Zootecnia, 2012)
The objective of this study was to evaluate the effect of reducing the crude protein (CP) with the use of amino acids in diets with the same amount of calories anddifferent levels of soybean oil (SO) for finishing pigs kept in two different ambient temperatures. A total of 120 barrows (initial weight of 68.0±1.9 kg) were utilized for the experiment. The design was of randomized blocks in a 2 × 3 × 2 factorial arrangement (two levels of CP, 16.2 and 13.7%; three levels of SO, 1.5; 3.0 and 4.5%; and two ambient temperatures, 19 and 31 ºC), totaling twelve treatments with five replicates for thirty days. The heat reduced feed intake (FI) of the animals, regardless of the levels of CP and SO used, and reduced weight gain (WG) in diets with reduced CP and SO or higher SO. The increased level of CP and SO improved feed conversion (FC) when the animals were kept in thermoneutral environment and given a diet with higher protein content. The reduction in CP increased FI only in the thermoneutral environment. In the heat, WG increased in diets with higher levels of SO, without influencing FC. The manipulation of diet and temperature did not affect most carcass traits. The SO reduced backfat thickness (BT) only in diets with high CP and animals kept in thermoneutral environment. The reduction of CP increased the BT only in diets with high content of SO, both in hot and thermoneutral environments. Heat reduces FI and the inclusion of SO does not improve performance or carcass characteristics in these conditions. The reduction in CP improves WG only in diets with high oil content; however, it increases BT. In thermoneutral environment, increasing the SO is beneficial for performance and carcass characteristics, except when diets with reduced CP are used. The reduction in CP improves performance only in diets with low oil content.